Genetic analyses of floating Ulva prolifera in the Yellow Sea suggest a unique ecotype. (20th September 2015) - Zhao, Jin; Jiang, Peng; Qin, Song; Liu, Xiaojie; Liu, Zhengyi; Lin, Hanzhi; Li, Fuchao; Chen, Huaxin; Wu, Chunhui
Abstract: Large-scale green tides caused by the green algae Ulva prolifera have occurred in the Yellow Sea every summer since 2007. The genetic variation and relationships at the intra-species level among floating and attached samples of U. prolifera collected from 2007 to 2011 were analysed using ISSR (inter-simple sequence repeat) markers. The results showed that all of the floating samples collected from the Yellow Sea during the past five years formed a single genetic entity that was different from the attached samples in intertidal zone. A SCAR (sequence characterized amplified region) marker highly specific to the floating samples of U. prolifera was identified and it showed that the same population dominated in the blooms from 2007 to 2013. In combination with the morphology and physiological features, the genetic analysis results suggested that a unique ecotype of U. prolifera was responsible for the largest green tides in the world. These findings indicated that attached U. prolifera along the coast does not seem to be the originator of the green tide in the Yellow Sea and gene flow between attached and floating populations does not readily take place.